Human papillomavirus circulating tumor DNA assays as a mechanism for head and neck cancer equity in rural regions of the United States - Windon, Melina; Haring, Catherine (Frontiers in Oncology, 2024)
The rates of human papillomavirus-positive oropharyngeal cancer (HPV-OPC) are rising worldwide and in the United States, particularly in rural regions including Appalachia. Rural areas face unique health challenges resulting in higher cancer incidence and mortality rates, and this includes HPV-OPC. The recent advent of highly sensitive liquid biopsies for the non-invasive detection of HPV-OPC recurrence (circulating tumor HPV DNA, HPV ctDNA) has been swiftly adopted as part of surveillance paradigms. Though knowledge gaps persist regarding its use and clinical trials are ongoing, the ease of collection and cost-effectiveness of HPV ctDNA make it more accessible for HPV-OPC survivors than usual surveillance methods of frequent exams and imaging. Herein, we discuss how implementing HPV ctDNA assays in rural regions of the United States provide one poignant example of how liquid biopsies can improve cancer care equity.